Analisis Interferensi Co-Channel Pada Kinerja Sinyal Yang Dipancarkan Access Point Wireless Fidelity (Wi-Fi) Menggunakan Metode Quality Of Service (QOS) Studi Kasus : Rumah Sakit Mitra Jambi - Selvia, Nova; Zaenal Abidin, Dodo; Nurhadi (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
In building a wireless network, it is necessary to have an Access Point device that emits a signal that functions as a data traffic regulator, so that it will allow many clients to connect to each other through the network. This research aims to analyze co-channel interference that affects the performance of the signal emitted by the Wireless Fidelity (Wi-Fi) access point at Mitra Jambi Hospital. Using the Quality of Service (QoS) method, this study evaluates network performance parameters such as Throughput, Packet Loss, Jitter and Packet Loss to identify the impact of interference on signal quality. Data was collected through direct measurements at various locations within the hospital, as well as statistical analysis to determine the relationship between interference levels and signal performance. The results show that co-channel interference significantly degrades signal performance, which negatively impacts user experience, especially in critical situations in a hospital environment.